Molecular structure and morphology of biomineral composites based on nanohydroxyapatite and hyaluronic acid - Severin, A. V.; Ivanov, P. L.; Kostina, J. V.; Khabarov, V. N.; Kalmykova, T. P.; Antonov, S. V. (Polymer science. Series B, 2016)
New biocomposites based on hydroxyapatite and hyaluronic acid are obtained, and their structural and morphological characteristics are studied. With the use of a set of physicochemical methods, the effect of hyaluronic acid as an active medium in the synthesis of hydroxyapatite used to produce synthetic biocomposites close in structure to native hydroxyapatite is investigated.